A Guideline for Developing Administrators’ Digital Competence in the Next Normal Era at the Kampong Chhnang Provincial Teacher Training Center, Cambodia - Sokveasna Srey; Warabamrungkul, Theerangkoon; Wongpa , Jakrapan; Nilkote, Reongwit (Journal of Roi Kaensarn Academi, 2024)
Kampong Chhnang Provincial Teacher Training Center (PTTC) lacks digital competence and was unprepared to adjust to the COVID-19 crisis. Even though the Ministry of Education, Youth, and Sport (MoEYS) put efforts into developing online platforms such as Google Meet and Zoom and encouraged the administrators, educators, and trainers to use them, the performance was still low, and their administrative management is still carried out using conventional methods with little support from information and communication technology (ICT) facilities. This research aimed to: 1) study administrators’ digital competence in the next normal era at Kampong Chhnang Provincial Teacher Training Center, Cambodia, 2) analyze the administrators’ digital competence at the center, and 3) offer a guideline for developing administrators’ digital competence in the next normal era at this center. The researcher used the qualitative method to conduct the study which included in-depth interviews and focus group discussions with 15 key informants, consisting of 7 administrators, 4 technical supervisors and 4 teacher trainees who were selected by purposive selection according to the inclusion criteria. The data were analyzed using content analysis and presented in a descriptive style. The results of the research were as follows: 1) the administrators had a positive attitude toward developing digital competence in the following five main areas: information and data literacy, communication and collaboration, digital content creation, safety, and problem solving.​ This was due to the fact that they have used online platforms as sources of information and methods of communication; 2) it was found that the actual competence in these areas was limited and that improvement was necessary in order for them to use digital technology more efficiently and proactively; and 3) the guideline for developing the administrators’ digital competences in the next normal era at Kampong Chhnang Provincial Teacher Training Center, Cambodia consisted of three main factors: stakeholder support, teacher training center policy and strategic plan, and administrators’ personal visions. Based on the results above, the administrators need to be supported in terms of building the skills regarding using digital technology. Therefore, the guideline developed by this study is one of the tools that help them develop their digital competence and engage themselves more effectively and proactively.